Faith and fury : Eli Farmer on the frontier, 1794-1881 - Case, Riley B. (Indiana Historical Society Press, 2018)
"Faith and Fury by Riley B. Case tells the fascinating story of Eli Farmer (1794-1881) who moved to Monroe County, Indiana, in 1820 and became a Methodist circuit rider. Over nine years, he visited 33 different preaching locations and covered over 300 square miles in southern and central Indiana. Farmer was also a War of 1812 veteran, farmer, businessman, newspaper editor, Civil War chaplain, freemason, and state senator. Throughout his life, he was fascinated by the personal journey of faith and concerned himself with the spread of religion on the frontier. He wrote prolifically, including editorials and journals from the viewpoint of an "outsider" who rejected the institutionalization of churches with set doctrines, paid ministries, and lavish buildings. Farmer was a primary organizer of the Methodist circuit until his break with the denomination in 1839. This study by Case draws heavily on Eli Farmer's vivid memoirs, which he dictated after the Civil War. The Second Great Awakening contributed significantly to Indiana's early history. Political dissension in the new republic over the power of government as opposed to individual liberty helped fuel religious fervor on the frontier as it opened for settlement. Constitutional ideas of freedom and equality supported Protestant denominations proclaiming that people had free will and could speak to God personally. As settlers flocked to these congregations, the frontier culture favoring self-reliance gave way to the stabilizing effect of mainstream churches and two-party politics. Nevertheless, competing notions of individualism and strong government have both maintained popular support into the twenty-first century, making them particularly relevant topics to visit today"--